Right-wing authoritarianism, social dominance, system justification, and conservative political ideology as predictors of mental health stigma : The Hungarian case - Szabó, Zsolt Péter; Lönnqvist, Jan-Erik; Lantos, Nóra Anna; Valtonen, Jussi (Sage, 2024)
Background: Insights from mental health stigma research indicate the importance of societal and political views on mental health perceptions. Most studies originate from typical Western neo-liberal settings and focus on generic mental health issues. Our research explores these associations in Hungary, an understudied post-communist context with significant stigma levels, examining a broad range of stigmas related to both general and three specific mental illnesses: schizophrenia, depression, and alcohol use disorder (AUD). Aims: The study aims to connect a wide array of political dispositions to stigma associated with both general and specific mental illnesses, exploring both attitudes and behavioral intentions. Methods: We surveyed 492 participants (147 males, 342 females) on their political dispositions, including Right-Wing Authoritarianism (RWA), Social Dominance Orientation (SDO), general and economic system justification, and conservative political ideology, and their attitudes toward general and specific mental illnesses. Regression analyses identified key political dispositions influencing stigma. Results: RWA was significantly linked to most stigma outcomes, while conservative political ideology showed a selective impact. Other predictors had minimal influence on stigma outcomes. Conclusion: Our findings suggest that perceptions of danger, threat, and unconventionality, as indicated by RWA, are crucial for mental health stigmatization in Hungary. Intervention programs should target these factors, particularly in similar contexts.
Keywords: mielenterveys; masennus; mielenterveyshäiriöt; Unkari; asenteet; sosiaalipsykiatria; stigmat; skitsofrenia